2011
DOI: 10.1002/14651858.cd002199.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Operative procedures for fissure in ano

Abstract: *The basis for the assumed risk (e.g. the median control group risk across studies) is provided in footnotes. The corresponding risk (and its 95% confidence interval) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI). CI: Confidence interval; OR: Odds ratio; GRADE Working Group grades of evidence High quality: Further research is very unlikely to change our confidence in the estimate of effect. Moderate quality: Further research is likely to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 44 publications
1
22
0
3
Order By: Relevance
“…Our study has shown a healing rate of 71 % at 6 weeks for topical diltiazem and a much superior rate for LIS (96 %). The healing rate for LIS as reported in other studies range from 92 to 100 % [5,23,24].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our study has shown a healing rate of 71 % at 6 weeks for topical diltiazem and a much superior rate for LIS (96 %). The healing rate for LIS as reported in other studies range from 92 to 100 % [5,23,24].…”
Section: Discussionmentioning
confidence: 84%
“…The American Society of Colon and Rectal Surgeons (ASCRS) recommend conservative management with stool softeners, high fibre diet and sitz bath as the initial line of management [4]. A Cochrane review of anal fissure treatment had shown that topical and injected therapies are only marginally effective to placebo therapy and recommended lateral internal sphincterotomy (LIS) as the gold standard for chronic anal fissure (CAF) [5]. The main drawback of LIS is the potential complication of incontinence to flatus or faecal matter.…”
Section: Introductionmentioning
confidence: 99%
“…Concluyendo que la esfinterotomia lateral interna abierta o cerrada parecen ser igual de eficaces. Considera además que la rigurosa medida de la esfinterotomia puede disminuir el riesgo de incontinencia 8 . …”
Section: Resultsunclassified
“…Para el grupo esfinterotomia a los 12 meses los porcentajes disminuyen hasta 4% en el mejor de los grupos, valor que es considerado elevado por los autores 8 .…”
Section: Discussionunclassified
“…the most recently published Cochrane reviews of therapy for anal fissure described 102 randomized trials. 2,3 in the current updates nearing completion, we will be adding more than 40 additional randomized trials. not a single one of those trials examined the efficacy of fissurectomy and botox in the treatment of anal fissure.…”
Section: Efficacy Of Fissurectomy and Botox For Chronic Anal Fissurementioning
confidence: 99%